Auditory-Motor Mapping Training in a More Verbal Child with Autism - Chenausky, Karen V.; Norton, Andrea C.; Schlaug, Gottfried (Frontiers in Human Neuroscience, 2017)
We tested the effect of Auditory-Motor Mapping Training (AMMT), a novel, intonation-based treatment for spoken language originally developed for minimally verbal (MV) children with autism, on a more-verbal child with autism. We compared this child’s performance after 25 therapy sessions with that of (1) a child matched on age, autism severity, and expressive language level who received 25 sessions of a non-intonation-based control treatment (Speech Repetition Therapy, SRT) and (2) a matched pair of MV children (one of whom received AMMT; the other, SRT). We found a significant Time x Treatment effect in favor of AMMT for number of Syllables Correct and Consonants Correct per stimulus for both pairs of children, as well as a significant Time x Treatment effect in favor of AMMT for number of Vowels Correct per stimulus for the more-verbal pair. Magnitudes of the difference in post-treatment performance between AMMT and SRT, adjusted for Baseline differences, were (a) larger for the more-verbal pair than for the MV pair and (b) associated with very large effect sizes (Cohen’s d > 1.3) in the more-verbal pair. Results hold promise for the efficacy of AMMT for improving spoken language production in more-verbal children with autism as well as their MV peers and suggest hypotheses about brain function that are testable in both correlational and causal behavioral-imaging studies.